Oxidation of sesbania gum using an octenyl succinate-esterified composite - Mingyan Wang; Dongfen Huang; Yue Sun; Jian Chen; Hengfu Huan; Guanglong Yao (International Journal of Food Properties, 2023)
In this study, sesbania gum (SG) was successfully modified by using H2O2 as the oxidant, CuSO4 as the catalyst, and octenyl succinic anhydride as the esterification agent. The effects of oxidation and esterification on the structure and properties of SG were investigated by Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and thermogravimetric analysis (TGA), among other techniques. By FTIR analysis it was found that the oxidation did not introduce new groups, while the ester carbonyl group was successfully introduced into the molecular chain of SG. The oxidation of SG by H2O2 involves the cleavage of long chains, which is also the main cause of its reduction in viscosity. Oxidation reduced the crystallinity of SG, and its crystal structure was found to be severely damaged after esterification. Both oxidation and esterification altered the thermal properties of SG, whereby the thermal stability and freeze-thaw stability of the modified SG were improved and the expansion capacity was effectively reduced.